Pengadaan Taman Pendidikan Al-Qur'an Literasi di Gampong Santan Kecamatan Ingin Jaya Aceh Besar - Dyah Erti Idawati; Raihan Dara Lufika; Izziah Izziah; Iskandar Abdul Samad; Atika Aditya (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
This community service was conducted in Gampong Santan, located in the Ingin Jaya District of Aceh Besar Regency, with the primary aim of renovating a space into an Al-Qur'an Education Park (TPA). The newly created space is specifically designed to serve as a dedicated area for Al-Qur'an literacy activities among the young community members. As is known, the level of Al-Qur'an literacy in Indonesia is in the moderate category, even though it is a country with the largest Muslim population in the world. Recognizing this gap, the community service project sought to address the issue by providing a dedicated and well-equipped space for the residents of Gampong Santan, particularly the younger generation, to engage in and develop their Al-Qur'an literacy skills. Therefore, the community service project sought to bridge the gap by providing a well-equipped facility in Gampong Santan. By revitalizing an underutilized space and transforming it into a hub for Al-Qur'an education, the project hoped to inspire and encourage the residents, particularly the youth, to deepen their connection with the Al-Qur'an.Keywords: TPA, Literacy, Community Service